Perspectives on teacher spirituality: an integrative review - Gonçalves Ferreira, Anderson; Brandão Viana, Helena (Revista Hipótese, 2025)
Studying the influence of teachers’ spirituality within the educational context has gained increasing importance in both Christian and non-Christian settings. The aim of this study was to conduct an integrative literature review in order to analyze national and international studies addressing teacher spirituality in the educational context, with an emphasis on Basic Education. For this purpose, searches were carried out in the scientific databases CAPES PERIÓDICOS, ERIC, and SCIELO over a five-year period, using the descriptors: “Spirituality” AND “Education” AND “Teacher.” After applying filtering criteria, 10 articles were selected for qualitative analysis. The studies reviewed emphasize that spirituality is not a secondary element, but rather a highly significant pillar of teaching practice, fostering resilience, professional ethics, and the quality of pedagogical practices, thus contributing to a more humanized and transformative education.
Keywords: Teacher; Basic Education; Spirituality